Tradisi Pesantren Sebagai Warisan Kebudayaan Islam dalam Pendidikan di Indonesia - Wulandari Berliana Sapyudin; Amalia Saharani; Imron Ashari; Vella Maftukhatul Khoiriyah (Jurnal Ilmu Sosial dan Humaniora, 2026)
As Islamic educational institutions, Islamic boarding schools (pesantren) play a crucial role in preserving and transmitting Islamic values ​​and culture to the younger generation in Indonesia. Amidst globalization and modernization, Islamic boarding schools are required to maintain their traditions while adapting to changing times. This study aims to understand the role of Islamic boarding school traditions as part of Islamic cultural heritage in education and to examine their relevance to contemporary education. The method used is qualitative research with a library research approach, reviewing various relevant sources. The study results indicate that Islamic boarding school traditions play a significant role in shaping character, instilling moral values, and strengthening Islamic cultural identity in society. Furthermore, Islamic boarding schools are able to keep pace with developments in modern education through the implementation of the national curriculum and the use of more innovative learning methods without abandoning their traditional, distinctive values. Therefore, the Islamic boarding school tradition must continue to be strengthened as an effort to preserve culture and develop Islamic education that remains relevant in facing global challenges today and in the future